Perlindungan Hukum terhadap Anak dalam Perkara Dispensasi Kawin di Kabupaten Bojonegoro Tahun 2020-2025 - Moch Tekad Reza Reganata; Sugiharto Raharjo Japar; Muhammad Fauzul Kabir; Fifi Firmanda Elva Thalia; Alviya Agustina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Despite the amendment of the minimum legal age for marriage under Law Number 16 of 2019, applications for marriage dispensation involving minors remain prevalent in various regions of Indonesia, including Bojonegoro Regency. This condition raises concerns regarding the effectiveness of child protection within judicial practices, particularly in the interpretation of “urgent circumstances” by religious courts. This study aims to analyze the implementation of child legal protection in marriage dispensation cases decided by the Bojonegoro Religious Court during the 2020-2025 period. The research employs a juridical-normative approach with a case-based analysis of court decisions, supported by statutory and doctrinal legal materials. The analysis is framed using Lawrence M. Friedman’s legal system theory to examine the interaction between legal substance, legal structure, and legal culture in judicial reasoning. The findings reveal that although normative regulations concerning marriage age and child protection are formally adequate, judicial practice tends to apply a broad interpretation of urgent circumstances, resulting in the frequent granting of dispensations. This approach indicates that legal culture and social considerations significantly influence judicial discretion, often outweighing the legislative objective of preventing child marriage. Consequently, the effectiveness of child protection through age limitation is highly dependent on the consistency of judicial interpretation in applying the principle of the best interests of the child.